Study on droop control method for islanded microgrid operation - Chiam, Tat Chern (Nanyang Technological University, 2023)
This research looks at how microgrids (MG) function and how distributed generators (DGs), such as batteries and microturbines, are increasingly used to meet local load demands. RES used in this study includes solar and wind energy. Power and frequency instability can be brought on by low inertia electrical systems, which can result from the incorporation of RES into MGs via power electronic interfaces. The lack of inertia brought on by the displacement of synchronous generators is not addressed by droop control, even though it has been recognized as a technique for controlling voltage and frequency. It is suggested that VSG control, which combines the swing equation with active power droop control, be used to handle this problem by adding inertia to the system, lowering frequency deviation, and enhancing power regulation.